The Relative Impact of Urinary and Sexual Function vs Bother on Health Utility for Men With Prostate Cancer. Issue 5 (25th May 2020) - Jeong, Chang Wook; Herlemann, Annika; Cowan, Janet E; Broering, Jeanette M; ten Ham, Renske M T; Wilson, Leslie S; Carroll, Peter R; Cooperberg, Matthew R
Abstract: Function and bother are related but distinct aspects of health-related quality of life. The objective of this study was to compare quantitatively the relative impacts of function and bother in urinary, sexual, and bowel outcomes on health utility as a reflection of health-related quality of life in men with prostate cancer. Our analysis included participants in the Cancer of the Prostate Strategic Urologic Research Endeavor utility supplementary study, with a final cohort of 1617 men. Linear regression on the patients' function and bother summary scores (0-100) from the University of California, Los Angeles Prostate Cancer Index was performed to predict bias-corrected health utilities. Urinary and sexual bother were associated with each health utility, and their coefficients were 3.7 and 20.8 times greater, respectively, than those of the corresponding function. To our knowledge, our study provides the first quantitative and direct comparison of the impacts of function vs bother on health utility.